Managing the International Reserve Assets in the Context of Debt Sustainability - Kondro Pavlo V. (Research Centre of Industrial Problems of Development of NAS of Ukraine, 2021)
The article is aimed at researching the adequacy of international reserve assets, their management in terms of ensuring debt sustainability, as well as financial-economic assessment of liquidity and solvency of the borrowing State. Based on the carried out study, it is determined that liquidity of the State, as a functional element of solvency of the State, provides for the ability of the State to mobilize the necessary resources, taking into account the transactional mechanism of asset transfer from one unit to another in order to ensure an adequate level of solvency of the debtor State. In addition, within the terms of the carried out analysis of the system infrastructure, it is worth noting that there is a relation between the solvency of the State and its liquidity, since the latter category is part of the first, but these concepts are not identical. The provision of international assets, as the dominant element of debt sustainability, acts through the mechanism of financial and monetary security, thus, an assessment of the adequacy of international assets in the part of sufficiency of their volumes to cover the needs of foreign trade operations, servicing and repayment of the State’s sovereign obligations to creditors must be done. A monitoring of the main indicative values of the assessment of the status and structure of international liquid assets and their relationship with economic indicators is carried out. Ways to improve the system of management of international reserve assets in order to ensure debt sustainability are proposed. Priority directions of future researches are allocated, which should be aimed at substantiate the impact of currency risks on the debt sustainability of the State.